2014
DOI: 10.1016/j.ultsonch.2013.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Radical production inside an acoustically driven microbubble

Abstract: The chemical production of radicals inside acoustically driven bubbles is determined by the local temperature inside the bubbles and by their composition at collapse. By means of a previously validated ordinary differential equations (ODE) model [L. Stricker, A. Prosperetti, D. Lohse, Validation of an approximate model for the thermal behavior in acoustically driven bubbles, J. Acoust. Soc. Am. 130 (5) (2011) 3243-3251], based on boundary layer assumption for mass and heat transport, we study the influence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 49 publications
(83 reference statements)
0
20
0
Order By: Relevance
“…This phenomenon is known as the bubble collapse. The generated extreme conditions are exploited by many industrial applications including sonochemistry [5][6][7][8][9][10], food processing [11][12][13] or even medical treatment [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon is known as the bubble collapse. The generated extreme conditions are exploited by many industrial applications including sonochemistry [5][6][7][8][9][10], food processing [11][12][13] or even medical treatment [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Sharp temperature increases around 40 and 80 μ s in Fig. S8 (b ) correspond to the bubble-collapse events, at which temperature inside bubble reaches ~10,000 K; this is acceptable because it was experimentally shown that temperature inside bubble could reach near 10,000 K at bubble collapse 29 for a single-bubble case, and this ultrahigh temperature field has been used for various chemical reactions 15 16 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Promotion of chemical reaction by ultrasonic wave has been studied in the field of sonochemistry, where cavitation bubbles generated by ultrasonic wave are deeply related to sonochemical reactions 10 11 12 . Sonochemical reaction is principally a decomposition reaction for organic substances 13 14 : Ultrasonic cavitation bubbles repeat growth and collapse, and significant temperature increase (up to thousands of kelvins) occurs at the collapse, which promotes the pyrolytic decomposition of the soluble substances near the hot spot and also produces free radical species from water that oxidize the substances 15 16 17 . Such a sonochemical reaction has been also used in the study of amyloid fibrils to fibrillate aggregates for obtaining the seeds 2 18 .…”
mentioning
confidence: 99%
“…The first test model is the periodically excited Keller-Miksis equation that is a second order ordinary differential equation describing the radial pulsation of a single spherical gas bubble placed in an infinite domain of liquid [38]. During the radial oscillation of the bubble, due to the external forcing, its contraction phase can be so rapid (collapse) that the temperature inside can reach thousands of degrees of Kelvin inducing chemical reactions [39][40][41]. Therefore, this model is extensively used in the field of sonochemistry [42][43][44][45][46][47][48][49][50][51] to estimate the collapse strength and the chemical yield of a single bubble.…”
Section: The History Of the Choice Of The Test Modelsmentioning
confidence: 99%